Upside down : [large type] a novel - Steel, Danielle (Random House Large Print, 2024)
While her mother, Oscar-winning actress Ardith Law, a Hollywood icon at 62, deals with conflicting feels for a much-younger man, her daughter, Morgan, a successful plastic surgeon in NYC, falls for a much-older man, which brings them together as they each try to navigate an unconventional romance.